L'archivio delle Minime Ancille della Santissima Trinità o Montalve alla Quiete di Firenze Inventario (1555-1886) - Giagnoni, Nicola (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2022)
Eleonora Ramirez de Montalvo is one of the most important historical figures of woman's assistance and education during the seventeenth century. She is the founder of two lay congregations: the Minime Ancille of the Divine Incarnation (1647) and the Minime Ancille of the Holy Trinity (1650). This volume lists and describes in an analytical way the papers produced and preserved by the second of these, also known Montalve alla Quiete, which for over two centuries carried out an intense activity and exerted a considerable influence in Tuscany. The study of this archive provides a unique range of information both on the economic and political events, and on the relationships maintained by the Montalve with society growing its prestige and heritage. It also offers the opportunity to undertake countless historical research on facts that concern Florentine territory and the rest of Tuscany.